Techno-Economic and Life-Cycle Assessment of Hydrogen-Ammonia Fuel Blends in Tugboat Engines for Sustainable Port Operations - Bayer, Muhammed Umar; Bilgili, Levent; Alkan, Sabri; Atak, Ustun; Celik, Veli (Mdpi, 2025)
The maritime sector, responsible for approximately 3% of global greenhouse gas (GHG) emissions, is under growing pressure to transition toward climate-neutral operations. Significant progress has been made in developing sustainable fuels and propulsion systems to meet these demands. Although electric propulsion and fuel cells are highlighted as key technologies for achieving net-zero carbon targets, they remain an immature solution for large-scale maritime use, particularly in long-distance shipping. Therefore, modifying internal combustion engines and employing alternative fuels emerge as more feasible transition strategies, especially in short-sea shipping and port applications such as tugboat operations. Among alternative fuels, hydrogen (H2) and ammonia (NH3) have emerged as the most prominent fuels in recent years due to their carbon-free nature and compatibility with existing marine compression ignition (CI) engines with only minor modifications. This study explores the viability of hydrogen and ammonia as alternative fuels for CI engines in terms of technological, economic, and environmental aspects. Also, using a life cycle assessment (LCA) framework, this study examines the environmental impacts and feasibility of gray, blue, and green hydrogen and ammonia production pathways. The analysis is conducted from both well-to-tank (WtT) and tank-to-wake (TtW) perspectives. The results demonstrate that green fuel production pathways significantly reduce emissions but lead to higher economic costs, while intermediate blends offer a balanced trade-off between environmental and financial performance. Moreover, the combustion stage analysis indicates that H2 and NH3 provide substantial environmental benefits by significantly reducing harmful emissions. Consequently, a Multi-Criteria Decision Making (MCDM) approach is employed to determine the optimal blending strategy, revealing that a 24% hydrogen and 76% marine diesel oil (MDO) energy share yields the most favorable outcome among the evaluated alternatives.
Keywords: port operations; sustainability; life cycle assessment; hydrogen; ammonia; fuel blend; MCDM